ANALYSIS OF THE ROLE OF EDUCATION AS HUMAN RESOURCES IN PREPARING THE GENERATION OF SOCIETY 5.0: ANALISIS PERANAN PENDIDIKAN SEBAGAI SUMBER DAYA MANUSIA DALAM MEMPERSIAPKAN GENERASI SOCIETY 5.0 - Saragih, Angellia (UPMI Proceeding Series, 2023)
Education has an important role in the information and knowledge era, where rapid changes occur in many areas of life. Mind, knowledge and organization are important factors in the information and knowledge age. Society 5.0 is based on the concept of integration between humans and technology, in which technology is used as a means to improve the quality of human life. In the current era of development, especially when faced with an increasingly globalized and competitive life situation, high-quality Indonesian human resources are urgently needed. Without having high Human Resources (HR) capabilities and being able to compete with other nations in the world, it will only lead to a disadvantageous position, especially in order to achieve an improved life. Especially nowadays, the millennial generation has its own challenges facing the revolutionary era of Digital Society 5.0. Most of them grow and develop through education, so that education becomes a vehicle for the development of the millennial generation. For this reason, competent human resources are needed as assets for the process of developing the millennial generation who are ready for problems and challenges. Thus, human resources become an important part of the process of developing education for the millennial generation. Therefore, in the era of society 5.0, the tendency of society to prioritize the role of systems that are converted by the role of humans in supporting educational activities.